Implementation Of Iot Water Saving Based On Smart Water Flow System - Hendra Fauzy; Solly Aryza; Adi Sastra Tarigan (INFOKUM, 2021)
Swimming pools and fish ponds require special care to maintain water conditions such as acidity, temperature, and water clarity. So far, the circulation of water in manual draining and filling takes too much time and requires electricity that must always be active. The problem in this study, designing an IoT system in water movement that can be monitored with variables of water acidity, water temperature, and water clarity. which can be controlled remotely. This tool is designed using Arduino and several sensors to process the system on the tool, Ultrasonic HC-SR04 to measure water level or water level, and Water Flow as a water volume recorder. The results of monitoring the water level will be displayed on the LCD. Furthermore, by using SIM800L it can be seen the position of the pump is on or off. Because SIM800L will send a message to the user to notify the reservoir is filled or empty. So that the user's cellphone will display information about the water volume, water level, and the state of the reservoir in a full or empty position.